(untitled) (Papeles, 2022)
The socio,environmental conflict of Nonogasta is related to a tanning industry, which for more than three decades has been polluting without any type of control and outside the Law. This conflict can be analyzed under the category of "sacrifice zone", referring to places with an unequal distribution of environmental costs. In this case, the profits from the leather´s sale belongs to the company, while the pollution remains in the territory. In the political debate, this conflict is addressed under a false dilemma: the “right to work” against the “right to live without contamination”. The present work addresses the inefficiency in the justice administration throughout a process we identify as a "pact of silence" forged on a network of different institutions and social actors that made invisible this socio,environmental conflict.